On Entrepreneurs and Entrepreneurship of the Olive-oil Economy in the Aegean: The Case of Lesvos Island - Sifneos, Evridiki (The Historical Review/La Revue Historique, 2005)
This article summarizes the conclusions of a study on entrepreneurial activities related to the cycle of the olive-oil economy in Lesvos, an island in the North-Eastern Aegean, from the eighteenth century until the middle of the twentieth century. It is based on research and observations drawn from a multiform primary material, such as companies’ records, communal and family archives, consular and administrative reports, as well as secondary sources which allow comparisons with other oleiferous regions and connect the economy of Lesvos to the broader Aegean and Mediterranean environment. It points out that the single cultivation phenomenon, though associated to the economy of risk, obeyed to the market’s command and was prepared by the abolition of the governor’s monopoly on the oil trading and the consequent opening of the market. This enabled the Christian ottoman subjects to develop the administration of intensive olive growing, mechanized oil extraction and trade expansion. Olive oil and soap were the two basic commodities of the island’s export revenues that were commercialised, despite their low quality, into a wide range of port and island markets of the Asia Minor coast, the Aegean islands and the Black Sea. Moreover, the article explores the type of commercial and industrial enterprises and the characteristics of the olive-cycle entrepreneurs. It concludes with the commercial crisis suffered from the major political and economic changes of the twentieth century and the consequent reorientation of Lesvos’ businessmen towards Crete and Piraeus, the olive manufacturing centres of the Neohellenic state.